Pengaruh Penerapan Pendidikan Karakter dalam Meningkatkan Nilai Disiplin dan Tanggung Jawab Siswa Kelas V SD Negeri Sungai Iyu) - Safrina Safrina; Muhammad Dani; Aminah Aminah (LPPM Institut Pendidikan Nusantara Global, 2026)
This research examines the influence of character education implementation on improving discipline and responsibility values among fifth-grade students at SD Negeri Sungai Iyu. Motivated by low parental involvement, lack of consistency in teachers' strategies, and limitations in character education effectiveness, this research aims to examine the influence of character education on student responsibility, investigate the relationship between discipline and responsibility, and analyze the relationship between character education implementation and responsible attitudes. Using a quantitative approach with a correlational survey method, this research involved 31 fifth-grade students, 3 teachers, and 31 parents at SD Negeri Sungai Iyu in the first semester of the 2025/2026 academic year. The research results show that the teachers' role is very positive (75%), while parents' responses show positive reactions, particularly in character education regulation (45.2%). The regulation of character education implementation contributes to an increase in discipline by 0.285. A Pearson correlation coefficient of 0.468 (p = 0.008) was found, proving a positive and significant relationship between character education and students' discipline and responsibility values. Simple linear regression analysis also confirms that character education has a significant influence of 21.9% on discipline and responsibility (Y = 16.235 + 0.285X). This indicates that character education is an effective instrument for developing responsible students.